Penggunaan Media Modifikasi Bola Plastik Berisi Pasir Untuk Meningkatkan Hasil Belajar Tolak Peluru Siswa Kelas VI SDN 13 Biru - Muliadi Muliadi; Sitti Jauhar (Universitas Negeri Makassar, 2022)
The purpose of this study was to describe the use of plastic balls filled with sand to improve learning outcomes for sixth graders at SD Negeri 13 Biru, Tanete Riattang sub-district, Bone district. This research is classroom action research (CAR). The implementation method is carried out starting from planning, action, observation/evaluation and reflection activities to obtain accurate information. The research subjects were sixth grade students of SD Negeri 13 Biru. The data collection technique in this study was observation and shot put test using the back and side of the repulsion. Data analysis techniques are data reduction, data presentation, conclusion drawing. The results showed that using a plastic ball filled with sand as the media could improve the learning outcomes of Class VI students of SD Negeri 13 Biru. This is evidenced by an increase in shot put learning outcomes before being given action with a low category/score increasing to a high category.